Penerapan Model Spiritual Leadership terhadap Peningkatan Kinerja Perawat - Hartati, Theresia; Bunga, Asnet Leo (Journal of Telenursing (JOTING), 2024)
This research aims to see how implementing the spiritual leadership model improves nurse performance. The research method used is a literature review through electronic databases and websites, namely Google Scholar, Science Direct, PubMed, and Semantic Scholar, with inclusion criteria including ten journals with the keywords "Spiritual Leadership" and "Nurse Performance." The research results show that spiritual leadership significantly affects nurse performance, which is mediated by affective commitment and job satisfaction. Spiritual values such as compassion and caring are essential in spiritual leadership and impact nurse performance. In conclusion, spiritual leadership is vital to improving nurse performance through increasing organizational commitment, work involvement, and motivation. Keywords: Nurse Performance, Spiritual Leadership